2018
DOI: 10.1029/2018ja025486
|View full text |Cite
|
Sign up to set email alerts
|

ARTEMIS Observations of Solar Wind Proton Scattering off the Lunar Surface

Abstract: We study the scattering of solar wind protons off the lunar surface, using ion observations collected over 6 years by the ARTEMIS satellites at the Moon. We show the average scattered proton energy spectra, directional scattering distributions, and scattering efficiency, for different solar wind incidence angles and impact speeds. We find that the protons have a scattering distribution that is similar to existing empirical models for scattered hydrogen energetic neutral atoms, with a peak in the backward direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 43 publications
(92 reference statements)
0
26
0
Order By: Relevance
“…A typical value of the compressibility of the SW fluctuations is about 0.03 and does not depend on the frequency through the inertial range (Šafránková et al, 2019). We assume that the enhanced compressibility can be caused by the modification of the SW wave field by a presence of ions reflected from the lunar surface (Harada et al, 2015;Lue et al, 2018). Surprisingly, a larger portion of compressive fluctuations is observed at the lower frequency (0.005 Hz, left panels).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A typical value of the compressibility of the SW fluctuations is about 0.03 and does not depend on the frequency through the inertial range (Šafránková et al, 2019). We assume that the enhanced compressibility can be caused by the modification of the SW wave field by a presence of ions reflected from the lunar surface (Harada et al, 2015;Lue et al, 2018). Surprisingly, a larger portion of compressive fluctuations is observed at the lower frequency (0.005 Hz, left panels).…”
Section: Discussionmentioning
confidence: 92%
“…Taken into account the way of the data selection and overall geometry, these distances correspond to measurements at the Moon dayside during periods of nearly radial IMF. We assume that the enhanced compressibility can be caused by the modification of the SW wave field by a presence of ions reflected from the lunar surface (Harada et al, 2015;Lue et al, 2018). It means that the mechanisms of the wave particle interaction would be similar to that in the FS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we note that analyses of Chandrayaan observations of reflected solar wind protons and a comparison of these observations to hybrid modeling found that a forward scattering function for protons off of crustal magnetic anomalies yielded the best fit to the data [ Lue et al , ; Fatemi , ]. The forward scattering of solar wind protons off of lunar magnetic anomalies is also distinctly different from solar wind proton scattering from the unmagnetized lunar surface, which has been observed as dominantly backscattered in both charged [ Saito et al , ; Lue et al , ] and neutral forms [ Schaufelberger et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…The backscattered H + ions appear to have a similar scattering function to that of the backscattered H-ENAs (Lue et al , 2018. However, there are clear differences in the energy spectra, where the H + ions have a higher mean energy than the H-ENAs (Lue et al 2014;Lue et al , 2018.…”
Section: Observations Of Particle Reflection From the Moonmentioning
confidence: 91%